Exploring the over-time, multifaceted impacts of three COVID-19 lockdowns on aspects of capability, wellbeing and mental health across vulnerabilities in Austria - Helter, TM; Łaszewska, A; Simon, J (Springer Nature, 2022)
The Austrian government imposed multiple major lockdowns during the COVID-19 pandemic, but the relevant measures and their perceptions varied over time. The aim of this study was to compare the over-time impacts of the three COVID-19 lockdowns between March 2020 and December 2021 for (capability) wellbeing and mental health in Austria. Adult Austrian residents (n = 87) completed an online survey about their experiences during three COVID-19 lockdowns, including capabilities (OxCAP-MH), depression and anxiety (HADS), and general wellbeing (WHO-5). Differences across the baseline and follow-up scores of these instruments were summarised by demographic/socioeconomic characteristics. Longitudinal comparisons of the impacts of the lockdowns were conducted using random effect models on panel data for overall instrument scores and individual capability items. The levels of (capability) wellbeing and mental health decreased for most respondents across the three lockdowns: average 2.4% reduction in OxCAP-MH scores, 18.8% and 9% increases in HADS depression and anxiety subscale scores respectively, and 19.7% reduction in WHO-5 score between the first and third lockdowns. Mental health treatment prior to the pandemic, social support and satisfaction with government measures were the most influential characteristics that determine the association with impacts of the chain of lockdowns. Our study is the first to assess the differential capability limiting aspects of lockdowns over time alongside their impacts on mental health and general wellbeing and calls for special attention for mental health patients, isolation and satisfaction with government measures.